Penerapan Sahur (Santri Sehat Tubuh Bugar) Dalam Mengatasi Permasalahan Kesehatan di Sekolah MAKN Bolmong - Meinita Wulansari; Nur Ainie Rabiasa; Indria Putri Utina; Sumarni Amir; Nur Afni Teapon; Sela Aprilia Mokodompit (Jurnal Insan Pengabdian Indonesia, 2023)
Clean and Healthy Living Behavior (PHBS) is a behavior in which a person applies hygiene behavior in his daily life by paying attention to his health level. Living a healthy life is something that everyone should practice because there are so many benefits, from mental and physical health to focusing on doing something, as well as on the welfare of family members and the creation of a beautiful, beautiful and peaceful atmosphere so that the living environment feels comfortable. The KKN student group at the Muhammadiyah University of Manado has a mission to make MAKN BOLAANG MONGONDOW students aware of the importance of implementing Clean and Healthy Behavior through several work programs related to PHBS. Some of the activities carried out were SAHUR (SANTRI HEALTHY BODY) and counseling on how to wash hands properly, which was carried out at the MAKN school in BOLAANG MONGONDOW sub-istrict, given the low awareness of the school community on the importance of health. As a result, through some of the activities above, it is able to make the school community aware of the importance of implementing Clean and Healthy Behavior and can provide knowledge to the community regarding how to apply clean and healthy living behaviors appropriately.